Penerapan Gel Ice Pack untuk Mengurangi Nyeri saat Dilakukan Chest Tube Removal pada Pasien Pascaoperasi Jantung - Ihsanidar, Yuniyas; Nurachmah, Elly; Adam, Muhamad; Yuningsih, Yuningsih; Khasanah, Siti Nur (Journal of Telenursing (JOTING), 2024)
The application of evidence-based nursing (EBN) aims to demonstrate the use of ice gel packs to reduce pain in post-cardiac surgery patients undergoing chest tube removal (CTR) in the Intermediate Surgical Ward of Harapan Kita Heart and Vascular Hospital in Jakarta in April 2024. The method used in this EBN application is a pre-posttest control group design, where each group consists of 9 respondents. The Mann-Whitney test results show a significant difference in pain reduction between the intervention group and the control group. In conclusion, post-cardiac surgery patients who received a cold compress using ice gel packs before chest tube removal (CTR) experienced minimal pain increase during the chest tube removal (CTR). Keywords: Chest Tube Removal, Pain, Post Cardiac Surgery